2018
DOI: 10.1111/bcp.13760
|View full text |Cite
|
Sign up to set email alerts
|

The influence of heart failure on the pharmacokinetics of cardiovascular and non‐cardiovascular drugs: a critical appraisal of the evidence

Abstract: Prescribing in heart failure (HF), a common disease state that predominantly affects the older population, is often a challenging task because of the dynamic nature of the condition, requiring frequent monitoring and medication review, the presence of various comorbidities, and the frailty phenotype of many patients. The significant alterations in various organs and tissues occurring in HF, particularly the reduced cardiac output with peripheral hypoperfusion and the structural and functional changes of the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 103 publications
(333 reference statements)
0
29
0
Order By: Relevance
“…It has been reported that this may be due to reduced drug clearance and reduced volume of distribution in patients with heart failure [33]. Of potentially major clinical relevance, there are also reports of patients with heart failure with a significantly prolonged elimination half-life (t ½ ) for oral furosemide (+ 70%); significantly reduced clearance (− 50%) after intravenous furosemide administration, although volume of distribution and t ½ were similar to values in controls; significantly shorter t ½ (− 44%) for carvedilol; and increased values for time to reach peak plasma concentration (+ 67%) and t ½ (+ 130%), and reduced clearance (− 75%), after oral enalapril administration in patients with heart failure [32]. Although the prothrombin time-international normalized ratio is known to be unstable when warfarin is used in patients with heart failure [14], the results from our study show that edoxaban pharmacokinetics and pharmacodynamics are not affected by acute heart failure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been reported that this may be due to reduced drug clearance and reduced volume of distribution in patients with heart failure [33]. Of potentially major clinical relevance, there are also reports of patients with heart failure with a significantly prolonged elimination half-life (t ½ ) for oral furosemide (+ 70%); significantly reduced clearance (− 50%) after intravenous furosemide administration, although volume of distribution and t ½ were similar to values in controls; significantly shorter t ½ (− 44%) for carvedilol; and increased values for time to reach peak plasma concentration (+ 67%) and t ½ (+ 130%), and reduced clearance (− 75%), after oral enalapril administration in patients with heart failure [32]. Although the prothrombin time-international normalized ratio is known to be unstable when warfarin is used in patients with heart failure [14], the results from our study show that edoxaban pharmacokinetics and pharmacodynamics are not affected by acute heart failure.…”
Section: Discussionmentioning
confidence: 91%
“…Although data for DOACs have been limited, there have been multiple reports showing irregular pharmacokinetics of other drugs in patients with acute heart failure [32]. For example, the peak plasma tolvaptan concentration after administration of 15 mg in patients with heart failure was 1.9 times higher than that in healthy people, and the area under the plasma concentration-time curve was 3.4 times higher.…”
Section: Discussionmentioning
confidence: 99%
“…Apixaban has low hydrosolubility [40,41], and therefore, the systemic expansion of interstitial fluid that happens in periodic temporary decompensations of heart failure cannot explain the reduced plasma values. Other possible causes could be the systemic arterial hypoperfusion status, venous congestion, and neurohormonal activation, which negatively influences the integrity and function of the key organs, in particular the gastrointestinal tract, liver, and kidneys [42].…”
Section: Discussionmentioning
confidence: 99%
“…While many of these variables are not modifiable, the clinician must develop strategies to mitigate the risks. Pharmacodynamics and pharmacokinetics of commonly used medications are altered in end‐stage heart failure 25,34,35 and 20%‐40% of the population have an inadequate platelet response to clopidogrel, 24,36‐38 thus a novel approach to long term antiplatelet therapy is necessary. Cangrelor is an intravenous, short‐acting, reversible P2Y 12 antagonist that does not require hepatic activation making it an ideal agent in selected patients.…”
Section: Discussionmentioning
confidence: 99%